Management of Plant and Arthropod Pests by Deer Farmers in Florida. (15th July 2020) - Harmon, Laura E; Sayler, Katherine A; Burkett-Cadena, Nathan D; Wisely, Samantha M; Weeks, Emma N I
Abstract: Deer farming is a growing livestock industry. As with established livestock farming, biting arthropod pest control is a challenge, but knowledge about pest control practices being utilized by deer farmers is limited. To fill this knowledge gap and to assess if recommended integrated pest management (IPM) programs were being used, we surveyed Florida deer farmers about their pest management programs via an online questionnaire. Of surveyed deer farmers in Florida, 94% reported using chemicals for plant and arthropod pest control. Deer farmers reported controlling biting midges, mosquitoes, horse flies, and deer flies as their target arthropods. The primary herbicide and arthropod-targeted pesticide reported were glyphosate and permethrin, respectively. Two thirds of deer farmers reported that they were concerned about pesticide resistance developing on their properties, and 72% reported utilizing resistance mitigation techniques such as alternating pesticides or using less pesticide at the start of a management routine. A majority, 66%, of deer farmers reported using a combination of control techniques. Future work should focus on best management practice development based on the study findings, as well as educational materials regarding IPM use for deer farmers. Together these tools should improve animal health and well-being on deer farms by facilitating safe and sustainable arthropod management.